ANÁLISIS FINANCIERO EN LA COOPERATIVA DE AHORRO Y CRÉDITO “JARDÍN AZUAYO LTDA.” SUCURSAL – SARAGURO DEL CANTÓN SARAGURO, PROVINCIA DE LOJA. PERIODOS 2015-2016 - Salinas Serrano, Lady Andrea (2018)
Thesis work entitled: FINANCIAL ANALYSIS IN THE SAVINGS AND CREDIT COOPERATIVE "JARDÍN AZUAYO LTDA." BRANCH- SARAGURO DEL CANTÓN SARAGURO, LOJA PROVINCE. PERIODS 2015-2016, was executed in compliance with one of the requirements established in the Academic Regulations in force prior to opting for the degree of Accounting Engineering and Public Accountant-Auditor Audit. In order to comply with the specific objectives, the composition and structure of the financial statements were evaluated, which allowed executing the vertical analysis of each study period, allowing knowing the degree of representation of each account with respect to its item and its group so that it is known if the cooperative has an equitable distribution of its assets according to its financial and operational needs; In addition, the horizontal analysis was carried out in which the variations suffered by the accounts were determined, which could be the increases or decreases in the figures in the financial statements from one period to another. Likewise, the financial indicators established by the Superintendence of Popular and Solidarity Economy (SEPS) were applied, which allowed measuring and knowing the real state of the cooperative by means of a diagnosis of its main ratios such as Structure and Quality of Assets, Microeconomic Efficiency, Profitability, Financial Intermediation, Financial 5 Efficiency, Liquidity and Vulnerability of the Equity, the same ones that are graphed and reflected with their respective interpretation in each financial reason. Finally, the final report is made, which is of vital importance for managers and administrators, in which the results of the financial analysis are presented with their proper conclusions and recommendations in order to help in the correct decision-making. As a more relevant conclusion, the Savings Bank Credit Cooperative Garden Azuayo Ltda., Branch Saraguro, maintains an adequate distribution of its resources, so that most of its assets are constituted by loan portfolio, as in Liabilities obligations with the public since its main activity is the financial intermediation between the collection of resources of the depositors and the placement of the same through the credits, which are duly provisioned for their protection against the possible risk of uncollectibility; Likewise, it is important to highlight the adequate management in the recovery of credits in a special way in 2016, where its delinquency rate decreased to 1.96%, remaining within the established standard of ≤ 5%, which means that the resources placed in the different credit lines are being recovered efficiently.